Atuação de equipes gestoras para o ensino da matemática nos anos iniciais - Arantes, Antonio Carlos (2019)
This research aims to identify, describe and understand the role of management teams that can favor the performance in mathematics in the initial years. For this, a qualitative research was performed, of the interpretative type. The theoretical analysis was based on the researches already carried out on the subject and in Lück (2009), Libâneo (2004), Nóvoa (1995) and used the technique of triangulation of the data with a corpus of analysis constituted from a mixed questionnaire and semi-structured interview Management teams and official documents on schools and managers. The questionnaire was applied to the management teams of six schools in the municipal Education network of Sorocaba, selected from two criteria: (1) Increasing notes in mathematics in the 2011, 2013 and 2015 editions of the Brazil test; (2) IDEB on the rise and above the target foreseen by INEP in the 2015 edition. To deepen the data, after analyzing the questionnaires, considering that the six schools were identified with actions aimed at mathematics, we opted to interview the management teams of two school units, the largest and the lowest percentages of learning considered appropriate in mathematics, according to INEP. As a result, after triangulation of data from interviews, questionnaires and documents, we found that the schools surveyed have management teams that participate in the teaching and learning process with intentional actions such as attribution of Classes of 4th and 5th years to professors with higher affinities with mathematics, continuing teacher training, planning and replanning of pedagogical actions, valuation of HTP, stimulus to clear organizational communication and collaborative work as well as financial support for projects. These actions may have contributed to the teaching of mathematics, keeping students ' performance in external assessments growing. The results also pointed to the need to offer the public power of continuing education for managers and teachers, highlighting the model that included the contributions of the group of expert trainers who worked in the municipal network.